VALIDITY AND RELIABILITY OF STANDARDIZED PATIENT ASSESSMENT FOR COMMUNICATION SKILLS FORMATIVE ASSESSMENT IN SECOND-YEAR MEDICAL STUDENTS (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the validity and reliability of standardized patients in assessing the communication skills formative assessment of second year Viet Duc medical students Pham Ngoc Thach University of Medicine.Methods: A cross-sectional study was conducted on 50 second-year Viet Duc medical students, 5 standardized patients, and 2 lecturers at the Center for Elaboration Competency and Innovation in Clinical Simulation at Pham Ngoc Thach University of Medicine, from June 2025 to June 2026. Standardized patients and lecturers independently assessed students’ communication skills using an “abdominal pain” scenario and a checklist with confirmed content validity by six experts (CVI = 0.96, CVR = 0.92). Validity was assessed using Spearman’s correlation coefficients and the Mann-Whitney U test. Inter-rater reliability (Inter-RR) and intra-rater reliability (Intra-RR) were evaluated using intraclass correlation coefficient.Results: Standardized patients showed strong correlations with lecturers scores in communication skills (r = 0.7-1.0; p < 0.01). There were no statistically significant differences in mean scores between standardized patients and lecturers (p > 0.05). Inter-rater reliability ranged from moderate to excellent (Inter-RR = 0.57-0.91). Intra-rater reliability of standardized patients after four weeks was good to excellent (Intra-RR = 0.72-0.95).Conclusion: Standardized patients are a valid and reliable assessment tool for evaluating the communication skills formative assessment of second year Viet Duc medical students.
Keywords: Standardized patient, communication skills, validity, reliability.